Providing the plant extract silymarin to lactating sows: effects on litter performance and oxidative stress in sows. (13th September 2016) - Farmer, C.; Lapointe, J.; Cormier, I.
Abstract : Silymarin is an extract from the plant milk thistle that was shown to have antioxidant and hyperprolactinemic properties. Taking into account the essential role of prolactin for lactating sows and the systemic oxidative stress occurring during lactation, it is of interest to investigate the potential beneficial effects of silymarin on lactating sows. A study was therefore carried out to determine the effects of providing either 1 or 8 g/day of the plant extract silymarin to lactating sows. Sows in first, second or third parity were fed conventional diets during gestation and, at farrowing, were assigned as controls (CTL, n =33), or were fed 1 g/day (SYL1, n =33) or 8 g/day (SYL8, n =33) of silymarin. The silymarin was provided in two equal amounts per day, and was fed throughout a 20-day lactation. The performance of sows and their litters was assessed and circulating concentrations of prolactin (days 7 and 18), urea (days 7 and 18) and oxidative status, via protein carbonyls and superoxide dismutase activity (day 18), were measured in sows. Milk samples were obtained on day 18 to measure standard composition. There was no effect of silymarin ( P >0.10) on circulating prolactin or urea, or on oxidative damage to proteins or antioxidant potential in sows. Lactation feed intake, backfat and BW of sows were unaffected by treatment ( P >0.10) as was the case for milk composition and piglet growth ( P >0.10). Results demonstrate that providing up to 8 g/day of the plant extract silymarin to lactating sows had no beneficial effects in terms of circulating prolactin concentrations or oxidative status of sows, or in terms of performances of sows and their litters.